2007
DOI: 10.3844/ajbbsp.2007.180.186
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore Pattern Identification of Tachykinin Receptor Selective Peptide Agonists: Implications in Receptor Selectivity

Abstract: Abstract:The mammalian tachykinin (TK) peptides and their three Neurokinin (NK1, NK2 and NK3) receptors represent an effector system with wide-ranging actions on neuronal, airway smooth muscle, mucosal, endothelial, immune, inflammatory and remodeling cell function. Recent clinical and preclinical data suggests the pathophysiological role of TKs in various diseases including asthma, emesis and depression. The TK-NK receptor interactions and overlapping functions mediated by each NK receptor indicate added ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…The docking data further correlate well with the pharmacophore pattern proposed by us for NK-2 agonists, 40 and a pharmacophore pattern complementarity has been observed in the ligand-receptor complex, wherein the aromatic side chain of Phe 6 is found to closely interact with an aromatic microdomain in the NK-2 receptor, and hydrophobic Leu 9 and Met 10 are found to interact with hydrophobic residues of the receptor (Figure 1). This is further in accordance with the hypothesis that the binding site will be complementary to the distribution of polar/nonpolar atoms of the ligands in their bioactive conformations.…”
Section: Discussionsupporting
confidence: 85%
“…The docking data further correlate well with the pharmacophore pattern proposed by us for NK-2 agonists, 40 and a pharmacophore pattern complementarity has been observed in the ligand-receptor complex, wherein the aromatic side chain of Phe 6 is found to closely interact with an aromatic microdomain in the NK-2 receptor, and hydrophobic Leu 9 and Met 10 are found to interact with hydrophobic residues of the receptor (Figure 1). This is further in accordance with the hypothesis that the binding site will be complementary to the distribution of polar/nonpolar atoms of the ligands in their bioactive conformations.…”
Section: Discussionsupporting
confidence: 85%
“…The docking data, further, correlate well with the pharmacophore pattern proposed by us for NK 3 agonists, and a pharmacophore pattern complementarity is observed in the ligand–receptor complex (Figure ). This is further in accordance with the hypothesis that the binding site will be complementary to the distribution of polar/nonpolar atoms of the ligands in their bioactive conformations.…”
Section: Discussionsupporting
confidence: 85%
“…The key peptide residues F6, L9, and M10, identified as being important for pharmacological function as well as being identified in our study as pharmacophore points, 66 were found to have significant interactions with the NK 3 receptor. The pharmacophore pattern complementarity is observed for the NK 3 /NKB complex with the three hydrophobic pharmacophores of NKB being bound to three predominantly hydrophobic pockets of the receptor.…”
Section: ' Resultsmentioning
confidence: 56%